Biocomposites: Silicon Micro‐ and Nanofabrication for Medicine (Adv. Healthcare Mater. 5/2013). Issue 5 (2nd May 2013) - Fine, Daniel; Grattoni, Alessandro; Goodall, Randy; Bansal, Shyam S.; Chiappini, Ciro; Hosali, Sharath; van de Ven, Anne L.; Srinivasan, Srimeenkashi; Liu, Xuewu; Godin, Biana; Brousseau, Louis; Yazdi, Iman K.; et al.
<x xml:space="preserve">Abstract</x> Silicon micro‐ and nanofabrication are used to create innovative biomedical technologies and provide a suitable means to support rapid clinical translation. The review on page 632 by Alessandro Grattoni and co‐workers covers a broad spectrum of silicon nanosystems ranging from diagnostics to therapeutics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>